Luciano Rocha Santana reviews the Book 'Sufre, luego importa', by Francisco Lara and Olga Ramos' - Luciano Rocha Santana (Universitat Autonoma de Barcelona. Facultat de Dret, 2016)
Luciano Rocha Santana (PhD In Moral Philosophy at the University of Salamanca) reviews the book: “Suffers, then Matters” by Francisco Lara and Olga Campos. The book addresses the ethical debate about the relationship between humans and non-human animals, in issues such as animal testing and bullfighting.